Urban Touch - Sickinger, Edda (Arts Research Africa, The Wits School of Arts, University of the Witwatersrand, 2020)
The lecture-demonstration URBAN TOUCH understands the prolific practices of screening dance as a way of touching. “Touching” holds a double character as (1) getting into contact and (2) affecting or being affected. To touch, we have to move and the action of projecting helps the dance work move and relate in time and space.[1] While any surface can potentially transform into a screen,[2] the moment of screening creates an ephemeral social entanglement of movement, memory, relation, and affect.
The lecture-demonstration URBAN TOUCH understands the prolific practices of screening dance as a way of touching. “Touching” holds a double character as (1) getting into contact and (2) affecting or being affected. To touch, we have to move and the action of projecting helps the dance work move and relate in time and space.[1] While any surface can potentially transform into a screen,[2] the moment of screening creates an ephemeral social entanglement of movement, memory, relation, and affect.
Keywords: artistic research, arts research, decolonisation, arts pedagogy